Workplace Industrial Relations in Britain: The DE/PSI/SSRC Survey - Bélanger, Jacques (Labour / Le Travail, 1985)
This article reviews the book, "Workplace Industrial Relations in Britain: The DE/PSI/SSRC Survey," by W. W. Daniel and Neil Millward.
Keywords: DANIEL, W. W.; Industrial relations; MILLWARD, Neil; Nonfiction; REVIEWS; WORKPLACE Industrial Relations in Britain: The DE/PSI/SSRC Survey (Book); books